2021
DOI: 10.3390/plants10010091
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variability Largely Affects the Leaf Metabolomics Response to Isosmotic Macrocation Variations in Two Divergent Lettuce (Lactuca sativa L.) Varieties

Abstract: Mineral elements are essential for plant growth and development and strongly affect crop yield and quality. To cope with an everchanging environment, plants have developed specific responses to combined nutrient variations. In this work, we investigated the effects of multifactorial treatments with three macrocations (K, Ca, and Mg) on lettuce (Lactuca sativa L.) varieties that strongly diverge in leaf pigmentation (full red or green). Specifically, we monitored main leaf parameters and metabolomics profiles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…According to this composite indicator, a genotypic difference was evident, with the RS having a statistically higher value, while differences among NSs were very small. Although the concentration of the analyzed mineral elements was well above those expected to give deficiency symptoms, previous works indicated that isosmotic macrocation variation also influences yield (Fallovo et al, 2009;Corrado et al, 2021). Therefore, the higher nutrient UtE (in terms of dry biomass production) of a plant was also evaluated considering the fresh mass of the edible products.…”
Section: Discussionmentioning
confidence: 99%
“…According to this composite indicator, a genotypic difference was evident, with the RS having a statistically higher value, while differences among NSs were very small. Although the concentration of the analyzed mineral elements was well above those expected to give deficiency symptoms, previous works indicated that isosmotic macrocation variation also influences yield (Fallovo et al, 2009;Corrado et al, 2021). Therefore, the higher nutrient UtE (in terms of dry biomass production) of a plant was also evaluated considering the fresh mass of the edible products.…”
Section: Discussionmentioning
confidence: 99%
“…Wild lettuce has green leaves that accumulate anthocyanins at the edge of the lamina, and the red color in the cultivated lettuce germplasm was fixed by breeding [49]. A metabolomics comparison between red and green butterhead varieties also implied that breeding for leaf color selected and fixed compounds that vary little according to mineral nutrition [35]. Green cultivars may have different responses because various green varieties, such as GSB, do not develop red pigments when stressed [49].…”
Section: Discussionmentioning
confidence: 99%
“…This work was carried out with two differently colored baby leaf varieties, either green or full red [30]. While several studies have focused on green leaf lettuce [31,32], recent evidence indicated that not only the phytochemical constituents but also the morpho-physiological and metabolomic response to stress may differ between the lettuce cultivars with differently pigmented leaves [29,[33][34][35]. Although severe NaCl stress causes detrimental effects on plant growth and yield, more limited salt concentrations can be deliberately employed to improve the content of beneficial compounds and crop adaptation to stress [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The ambient temperature behavior was different for the three crops. However, the temperature and relative humidity values were nearly within the value range for lettuce growing, 17-22 • C for daytime and 3-12 • C for nighttime [45], the suggested average ambient temperature is 23.4-24 • C with relative humidity of 65% [46].…”
Section: Image Capturingmentioning
confidence: 70%
“…Besides, diverse non-invasive optical spectroscopic techniques, including Raman and Elastic spectroscopy, have been used for plant physiology monitoring and assessment [39,40]. Alternatively, optical parameters, such as spectral reflectance indexes, have been employed as a non-invasive technique in lettuce physiology assessment [41][42][43][44][45][46] for early-stage detection of Botrytis cinerea after 12, 18, 36, 60 and 84 h [47].…”
Section: Introductionmentioning
confidence: 99%